Pengembangan Sistem Informasi Manajemen Prakerin (Studi Pada: SMK Muhammadiyah 1 Malang) - Fahmi Aquinas; Satrio Agung Wicaksono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Internship become an important instrument in order to be able to produce competent workforce for students. SMK Muhammadiyah 1 Malang, as vocational school education in Malang city has collaborated with several industry parties to be able to assist students in carrying out maximum internship activities. However, in handling the implementation process of the internship there are problems such as forms that are still in the form of printed paper which can cause the data to be missing due to others and so on. So based on the existing problems, this research develops the management information system of internship in the process of implementing internship activities at SMK Muhammadiyah 1 Malang. In the research process applying the method of System Development Life Cycle (SDLC) iterative models without the process of deployment system. The method of interviewing and observing examples of physical documents is a form of method that used in the requirements system phase that produces admin and students as users. PHP programming language is implemented in the system development process by using the CodeIgnitier framework as a help. In the results of testing the system, a conclusion is drawn on the white-box testing that the algorithm has been tested valid and has 24 independent paths. In the conclusion of black-box testing that the functional requirements of the system are valid. While the results of user acceptance testing reveal that the system can be accepted by users very well with the final result of users acceptence is 91.87%.